Functions and Regulation of Circular Dorsal Ruffles - Hoon, Jing-Ling. (2013)
Cells construct a number of plasma membrane structures to meet a range of physiological demands. Driven by juxtamembrane actin machinery, these actin-based membrane protrusions are essential for the operation and maintenance of cellular life. They are required for diverse cellular functions, such as directed cell motility, cell spreading, adhesion, and substrate/matrix degradation. Circular dorsal ruffles (CDRs) are one class of such structures characterized as F-actin-rich membrane projections on the apical cell surface. CDRs commence their formation minutes after stimulation as flat, open, and immature ruffles and progressively develop into fully enclosed circular ruffles. These “rings” then mature and contract centrifugally before subsiding. Serving a critical function in receptor internalization and cell migration, CDRs are thus highly dynamic but transient formations. Here, we review the current state of knowledge concerning the regulation of circular dorsal ruffles. We focus specifically on the biochemical pathways leading to CDR formation in order to better define the roles and functions of these enigmatic structures.